Aprendizaje cooperativo en el desarrolllo del pensamiento lógico matemático de los niños de Educación inicial - Rizzo Moreira, Alida Beatriz (2021)
This research is based on developing logical mathematical thinking in early childhood children of the "Isabel la Católica" Educational Unit, through cooperative learning, explaining its importance in methodological processes. All of this could be done through exploratory research and observation. The research is based on cooperative work through various mathematical activities that allowed us to see in a direct way how mathematical logical thinking affects children from initial. Always respecting their way of thinking and analyzing the problems presented before. It should be borne in mind that cooperative learning is a fundamental practice that has been taking place for a long time, being considered a very helpful tool to achieve that meaningful learning in all students from their own ideas and knowledge. Cooperating helps the student to integrate more every day with his classmates and in that way to develop all his skills that he has already achieved and those that he has to achieve, on the other hand, working as a team turns out to be of great help for the teacher in any activity that the student is doing. Finally, based on the recommendations, the proposal was made that aims to specify all the scientific, psychological, methodological, and pedagogical aspects to implement the development of logical thinking